2016
DOI: 10.1515/aep-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium studies on adsorption of Reactive Blue 19 dye from aqueous solutions by nanohydroxyapatite adsorbent

Abstract: Abstract:In the present study the adsorption of Reactive Blue 19 dye on the hydroxyapatite (HAp) nanopowders was investigated. The batch adsorption experiments were performed by monitoring the adsorbent dosage, contact time, dye solution concentration, pH and temperature. At pH 3 and 20ºC, high dye removal rates of about 95.58% and 86.95% for the uncalcined and calcined nanohydroxyapatites, respectively, were obtained. The kinetic studies indicated the dye adsorption onto nanohydroxyapatite samples to follow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Thus, the experimental and modeling results indicated that T. conoides-derived biochar could be a practical and valuable sorbent to reactive dye-bearing wastewater. Magnetite/Graphene oxide nanocomposite (prepared from coprecipitation method) 62.5 [41] Nanohydroxyapatite (prepared from wet chemical precipitation method) 90.1 [42] Pineapple (Ananas comosus) leaf powder 42.0 [40] Prosopis juliflora-derived biochar (prepared from Peroxide-assisted microwave pyrolysis)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the experimental and modeling results indicated that T. conoides-derived biochar could be a practical and valuable sorbent to reactive dye-bearing wastewater. Magnetite/Graphene oxide nanocomposite (prepared from coprecipitation method) 62.5 [41] Nanohydroxyapatite (prepared from wet chemical precipitation method) 90.1 [42] Pineapple (Ananas comosus) leaf powder 42.0 [40] Prosopis juliflora-derived biochar (prepared from Peroxide-assisted microwave pyrolysis)…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it can be concluded that equilibrium was reached in several minutes, and the maximum amount of sorbed dye at native pH was 838.56 mg g −1 . Electrochemically synthesized sorbent (ECBBN) exhibits much higher sorption capacity for RB19 than other sorbents, especially than inorganic sorbents synthesized by conventional methods, such as precipitation, coprecipitation and hydrothermal methods, reported in previous studies (Table 2) [20][21][22][23][24][25][26][27]. Another advantage of the electrochemically synthesized sorbent is much lower sorption equilibrium time, which makes the sorption process considerably faster.…”
Section: The Ability Of Ecbbn To Remove Rb19mentioning
confidence: 94%
“…There are many studies of photocatalytic degradation of RB19 by diferent bismuth compounds used as photocatalyst [14][15][16][17][18][19]. Relative to the forego-ing techniques adsorption is considered to be simple, highly eicient and relatively inexpensive, and in a lot of studies, various organic and inorganic compounds are successfully used for removal of RB19 dye [9,[20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, optimal adsorption efficiency was determined by varying bed height (7.4 cm, 11.1 cm, 14.8 cm,18.5 cm, and 22.2 cm), pH (4 to 10), alginate:chitin ratio (1:2,1:3, 1:4, 1:5, 1:6, 1:7, 1:8, and 1:9), and dye concentration (20mg l -1 to 100 mg l -1 ). Removal efficiency of chitin is: …where C o is the initial concentration of methylene blue and C t is the solution concentration after adsorption at any time [6].…”
Section: Optimization Of Dye Adsorptionmentioning
confidence: 99%